A Real-time Schoolchild Shuttle Vehicle Tracking System Base on Android Mobile-apps - Forda Nama, Gigih; Halim Rasyidy, Fadillah; Arum S P., Raden; ., Mardiana (International Journal of Engineering and Technology, 2018)
Indonesians parent widely use private school shuttle services for their schoolchild due to their lack of time and effectiveness, unfortunately mostly of those shuttle vehicles (car or motor cycle) services currently cannot be tracked. From a security point of view, the parentâ€™s need a system that can identified the location of the vehicle in real-time. With rapid technological development today, parents' skepticism can be overcome by tracking the shuttle vehicles through a mobile applications that connected to Global Positioning System (GPS). This research presents the design of a prototype, called â€œAS-OJEKâ€, an android-based mobile apps and web technology for schoolchild shuttle applications that used several technology such as Web-services, JSON, PHP, MySQL and bootstrap framework as application builders. The application could be installed on any android smartphone version, it will be able to send the location and displaying the vehicle shuttle location on the smartphone screen and display historical location of the tracked vehicle. Rapid Application Development (RAD) framework was used as a software development method, with its 4 phases; phase 1: requirements planning and specifications, phase 2: user design, phase 3: construction, phase 4: cutover. The application was already appropriate with userâ€™s needs, proven by performing functional testing and User Acceptance Test (UAT). Based on the results of the UAT, this application has been running well and succeed sending vehicle location to the server, and can tracked through mobile-apps or web applications.Â